1997
DOI: 10.1111/j.1600-0749.1997.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Cloudman Mouse Melanoma Cells After Irradiation by Solar Wavelengths of Light

Abstract: A number of variants of Cloudman S91 mouse melanoma cells that differ with respect to the amount of pigment produced are available for study. In this report, we compare the photobiological responses of S91/amel, which contains about 1 pg of melanin per cell, with S91/I3, which contains about 3 pg/cell. Earlier studies had shown that UVC induced more oxidative damage (in the form of thymine glycols) in cell line S91/I3 than in S91/amel and that cell line S91/amel was more resistant to killing by UVC than S91/I3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The more heavily pigmented cells (S91/I3) contained 3 pg/cell of melanin and the lightly pigmented cells (S91/amel) contained 1 pg/cell. The more pigmented cells were considerably more sensitive to killing by UVB and UVA, but were less sensitive to killing by the polychromatic FS20 radiation (10). S91/mel contains 1.5 pg/cell of melanin, and is also less sensitive to killing by the three lamps compared to S91/I3 1 .…”
Section: Studies With Pigmented Mouse Cellsmentioning
confidence: 87%
“…The more heavily pigmented cells (S91/I3) contained 3 pg/cell of melanin and the lightly pigmented cells (S91/amel) contained 1 pg/cell. The more pigmented cells were considerably more sensitive to killing by UVB and UVA, but were less sensitive to killing by the polychromatic FS20 radiation (10). S91/mel contains 1.5 pg/cell of melanin, and is also less sensitive to killing by the three lamps compared to S91/I3 1 .…”
Section: Studies With Pigmented Mouse Cellsmentioning
confidence: 87%
“…It has been reported that more highly melanotic cell lines in tissue culture are not always protected more efficiently by melanin than are less melanotic cell lines against UV induced DNA photoproducts (Chalmers et al, 1976;Hill and Setlow, 1980;Huselton and Hill, 1990;Niggli, 1990;Schothorst et al, 1991;Yohn et al, 1992;Cieszka et al, 1997). This may result from the fact that only a small amount of melanin can be located over the nucleus because of the flattened morphology of cells in culture, and dispersed intracellular melanin cannot protect against DNA photoproduct formation as efficiently as supranuclear melanin caps observed in human epidermis in vivo (Kobayashi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these absorbance spectra, leucophores and melanophores should provide the most ultraviolet (UV) pho-Key words: Melanin, Pteridines, Photoprotection, Carote-toprotection to fish since the compounds they contain, ptenoids, Pigment cells, Fish ridines and melanin, correspondingly, have strong absorcaused complete mortality in cultured pigment cells lacking melanin (5). A more highly pigmented variant of a Cloudman mouse melanoma cell line was more resistant to cell killing than a lightly pigmented variant of the same type of cells when exposed to broadband ultraviolet light (8).…”
Section: Bances In the Uv Region Of The Spectrum Xanthophoresmentioning
confidence: 99%